The Future of Tropical Water Resources: Using Palaeolimnology to Inform Sustainable Management. - H, Hunt L.; A, Nankabirwa; D, Driessen T.; K, Mills; Lejju, Julius Bunny; B, Ryves D.; D, Jones M. (My University, 2000)
Lakes are an important resource. They provide vital ecosystem services and employment for many communities worldwide. Maintaining lakes as ecosystem providers without damaging the lake ecosystems themselves, against a background of increasing human use of landscapes and climate change, requires careful and informed management. Key to such management is an understanding of how lakes will respond to ongoing and future changes in their catchments. Long-term monitoring, through regular measurements of lake chemistry for example, can help provide this understanding but such data are rare, particularly for tropical lakes. Using a palaeolimnological approach can provide an alternative to long term monitoring. This paper compares the information that monitoring data and lake sediment records can bring to an understanding of lake change in western Uganda. Water chemistry data show a general pattern to lakes with higher Chlorophyll-a and TP values over the last 15 years, although not all lakes follow this pattern. Sediment cores from Lakes Kamunzuka and Nyungu both show changes in diatom flora through the latter half of the twentieth century and increases in dry mass accumulation rate between c. 1980 and 2000. This study highlights the importance of a co-ordinated monitoring approach to provide the data needed to benchmark management decisions. The importance of understanding each lake on its own merits, from a monitoring or palaeolimnological perspective is also highlighted. Combined, these approaches provide an approach to inform management decisions to sustain lake ecosystems in a healthy state, for the benefit of all users.
Keywords: Uganda; lakes; water chemistry; sediment cores; Diatoms